Etnoparenting in Bugis Tribe: (Parental Practices and Beliefs in the Karampung Indigenous Community, Sinjai Regency, South Sulawesi) - Nirwana Nirwana; Irmayanti Irmayanti (SEAMEO CECCEP, 2022)
Parenting based on local wisdom has long been an exciting topic. In addition to having a diversity of values and cultures, it can also significantly impact the formation of children's character. Later this method was known as ethnoparenting. This study explores the ethnoparenting tradition of the Bugis tribe in the Karampuang indigenous community, Sinjai Regency. By using an ethnographic approach, this research described or examined information based on practical experience and values ethnoparenting, then interpreted the data obtained from a psychological perspective. The subjects of this study were classifiedbased on the age of their children, namely parents who were pregnant with a gestation period of 7-9 months, parents who had children between 6 months to 1 year, and parents who had children of 2-3 years. This study showed that the tradition of parenting in the Karampuang indigenous community has started since pregnancy, various traditional rituals are believed to have meaning and influence on the growth of the children, the Karampuang indigenous community also believes that there are taboos that should not becarried out because they are against traditional values and will harm the child's growth. Indigenous peoples of Karampuang are famous for their cosmological values , which are also internalized in parenting practices. This study also explores parenting practices from various other dimensions, such as the philosophy of human development, mythology, spirituality. In addition, this study also concludes that the division of the roles of fathers and mothers in the parenting process is practiced based on the family's sociocultural values and situational conditions. Boys will follow their father more in daily functions, while girls will follow their mother's activities more. Meanwhile, the role of the community is implemented in thephilosophy of human development that emphasizes cooperation.